Treatment Outcomes and Toxicities of Multiple Tyrosin Kinase Inhibitors for Metastatic Medullary Thyroid Cancer: A Case Series - Marilda Mormando; Rosa Lauretta; Giulia Puliani; Marta Bianchini; Maria Elena Spoltore; Marialuisa Appetecchia (Biomedicines)
Background: The current possible treatments of advanced medullary carcinoma (MTC) include different drugs belonging to the class of tyrosine kinase inhibitors (TKIs): vandetanib, cabozantinb, and selpercatinib. Although the effects of these TKIs have been well described in clinical trials, the real-practice evidence of the effectiveness and safety of these treatment is scant. This real-world case series aims to describe a niche of patients with advanced MTC treated with more than one TKI by focusing on treatment responses and any reported adverse events (AEs) and to provide additional insight on the individualized approach to the management of metastatic MTC. Methods: Five patients with a diagnosis of metastastic MTC, treated with at least two different molecules of TKIs, were retrospectively selected. Results: Three patients obtained a partial response (one with cabozantinb, one with selpercatinib, and one with vandetanib), and two patients obtained disease stability (both of them treated with all three TKIs, the first two lines discontinued for AEs). The AE profile agreed with the known clinical trials AEs except for non-neoplastic ascites related to selpercatinib and lung cavitations of non-neoplastic tissue related to cabozantinb. The latter was an AE never described so far in patients receiving TKIs. Conclusions: The best management of MTC relies on an individualized approach, keeping in mind and dealing with the potential toxicity in order to minimize the treatment withdrawal.